Preclinical Experiments for Hypospadias Surgery: Systematic Review and Quality Assessment - Abbas, Tariq O.; Elawad, Abubakr; Kareem, Aamir; Pullattayil S, Abdul Kareem; Ali, Mansour; Alnaimi, Abdulla (Frontiers in Pediatrics, 2021)
Background There is a steadily growing number of different reconstructive hypospadias surgical procedures that were tested on animal models prior to their human application. However, the clinical translatability and reproducibility of results encountered in preclinical urethral reconstruction experiments is considered poor with significant factors contributing to poor design and reporting of animal experiments. Our objective is to evaluate the quality of design and reporting in published articles of urethral reconstructive preclinical studies. Methods Both PubMed and Embase databases were searched for animal urethral repair experiments between January 2014 and September 2019. Internal quality (bias) was evaluated through several signaling questions arising from Systematic Review Centre for Laboratory animal Experimentation (SYRCLE) while the quality of reporting was assessed by the Animal Research: Reporting of In Vivo Experiments (ARRIVE) guidelines by scoring of a 20-item checklist. Results A total of 638 articles were initially screened after the literature search. Employing the inclusion and exclusion criteria, 30 studies were chosen for full-text screening and 22 studies were considered eligible for the quality assessment. The mean score of the checklist was 66%. The elements that accomplished the highest grades included the number of animals utilized, the number in each investigational and control group, and the delineation of investigational conclusions. The items that least commonly stated comprised the information about the experimental method, housing and husbandry, rationalization of the number of animals, and reporting of adverse events. No paper stated the sample size estimation. Conclusion We found that several critical experiment design principles were poorly reported, which hinders a rigorous appraisal of scientific quality and reproducibility of the experiments. A comprehensive implementation of the ARRIVE guidelines in animal studies exploring tissue engineering for urethral repair is necessary to facilitate effective translation of preclinical research findings into clinical therapies.